Asymptotic Normality of the QMLE Estimator of ARCH in the Nonstationary Case - Jensen, Soren Tolver; Rahbek, Anders (Econometrica, 2004)
We establish consistency and asymptotic normality of the quasi-maximum likelihood estimator in the linear ARCH model. Contrary to the existing literature, we allow the parameters to be in the region where no stationary version of the process exists. This implies that the estimator is always asymptotically normal.